2013
DOI: 10.1155/2013/920130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidative Properties of N‐Acylamino‐Substituted Tricyclic Imides

Abstract: NewN-acylamino-substituted tricyclic imides have been screened for scavenging ability against the free radical 2,2-diphenyl-1-picryl-hydrazyl (DPPH•), chelating activity on ferrous ions, and reductive potential. The results were compared with synthetic antioxidants BHT, BHA, and Trolox. The compounds exhibited different levels of antioxidant activity in all tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, the bridged product 3a could be selectively reduced into the desired dihydropyrrole-fused product 3av in 81% yield and pyrrolidine-fused product 3aw bearing five contiguous stereocenters with complete stereospecificity and in 90% yield, respectively. Notably, pyrrolidine-fused bridged [2.2.1] skeletons are widespread in a variety of bioactive compounds . Importantly, excellent enantio- and diastereoselectivities (dr > 50:1) were achieved in all of these transformations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, the bridged product 3a could be selectively reduced into the desired dihydropyrrole-fused product 3av in 81% yield and pyrrolidine-fused product 3aw bearing five contiguous stereocenters with complete stereospecificity and in 90% yield, respectively. Notably, pyrrolidine-fused bridged [2.2.1] skeletons are widespread in a variety of bioactive compounds . Importantly, excellent enantio- and diastereoselectivities (dr > 50:1) were achieved in all of these transformations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…6 Hence, there is a growing request and interest for found and product of new antioxidants without harmful side effects in food and pharmaceutical applications. 7 Plants are main sources of compounds that act as antioxidant agents. 8 The important antioxidants that exist in plants are tocopherols and tocotrienols as fat-soluble antioxidants (vitamin E), folic acid (vitamin B9), Lascorbic acid (vitamin C), flavonoids as the largest natural phenols, carotenoids, phenyl acrylic acids and phenyl methanoic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Published reports revealed that other than phenolics, compounds with functionalities like carboxylic acid groups, long chains and olefins etc. may also chelate with metal ions [43,44] and thus serve as antioxidant agents. RP-UHPLC/MSanalysis of LP-M has disclosed the presence of several fatty acids, which must have been extracted in hexane fraction (LP-H), and thus impart highest chelating activities to the LP-H fraction.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%